Implementation of Information Services in Forming Discipline of Students in Class XI Phase F at Senior High School 4 West Sumatra (Sports Talent) - Jelara, Ica; Suryadi, Suryadi; Usman, Citra Imelda (ALACRITY : Journal of Education, 2025)
This research was motivated by the fact that there were students who were still attending class not according to the specified hours, there were students who were not dressed in uniforms according to the specified rules. The aim of this research is to describe: 1) An overview of discipline before information services are provided. 2) Description of discipline after being provided with information services. 3) Implementation of information services in forming discipline. The type of research used is an experimental method with a one group pretest and posttest research design. The population in this study was 72 and the sample used was 40 students taken using random sampling techniques. The instruments used in this research were questionnaires and documentation studies, while pretest & posttest percentage data analysis used interval scores and normality tests and t tests. The results of this research show: 1) Student discipline before being provided with information services is in the quite good category. 2) Student discipline after being provided with information services is in the good category. 3) There is a significant difference in student discipline before and after being provided with information services. There is an increase in the form of discipline in students in class XI Phase F SMA N 4 West Sumatra (Sports Talent) by providing information services. This research is recommended for guidance and counseling teachers. With the implementation of information services that have been carried out by researchers, guidance and counseling teachers are expected to be able to understand and improve the implementation of these services, then they can also apply them to students, especially in improving forms of discipline in order to improve their learning performance.